Nuteen: Langkah Awal Mendukung Program 8000 Hari Pertama Kehidupan: Nuteen: Initial Step to Support the First 8000 Days of Life Program - Inayah, Inayah; Metty, Metty; Indrayani, Novi; Pratama, Adams Bagus; Simanjorang, Eta Hosana Eka Rizti Boru (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Adolescents are an age group from children to adults who need good nutrition to create quality humans. The nutritional status of adolescents plays an essential role in the 8000 HPK and the future of the next generation. Based on previous studies in RT 007 Dusun Demangan, Ponogaran, Banguntapan, Bantul, there is no youth posyandu, only Paguyuban Muda Mudi. This association was formed to be involved in social activities. The formation of Nuteen is one way to form peer education or peer educators, which is expected to accelerate changes in healthy living behavior in anemia-free teenagers in preparation for 8000 HPK. Activities are carried out every Saturday afternoon. Activities will be carried out during June-December 2023. Providing education about anemia and the importance of maintaining food intake and nutritional monitoring practices for adolescents in preparation for 8000 HPK and independent calcal and outdoor discussions. Introduction of healthy, cheap, and nutritious local food with a demonstration and snack cooking competition to prevent anemia by teenagers. Giving pre and posttests to measure the level of knowledge of adolescents regarding anemia. The activity went well; 2 teenagers were anemic. Physical symptoms of anemia are felt by most teenagers. Local food ingredients can be applied in creating snack menus during competitions. Activities must be carried out routinely and continuously to improve adolescents' nutritional status and anemia status. The introduction of local food ingredients impacts references for healthy snacks for teenagers.